2013
DOI: 10.1614/wt-d-12-00126.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Multiple Rating Methods Utilized in Turfgrass Weed Science

Abstract: Turfgrass weed scientists commonly use visual ratings (VR) to assign a numerical value to a turfgrass or weed response. These ratings lack quantifiable numerical values and are considered subjective. Alternatives to VR, including line intersect analysis (LIA) and digital image analysis (DIA), have been used to varying extents in turfgrass research. Alternatives can be expensive, labor intensive, and can require extensive calibration and increased time for data acquisition. Minimal research has been conducted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 20 publications
8
19
0
Order By: Relevance
“…Pearson correlation coefficients showed a strong positive relationship between cover determined via visual estimates and lineintersect analysis in North Carolina at 15 (r = 0.97, P < 0.0001) and 46 (r = 0.92, P < 0.0001) WAIT, as well as in Texas at 16 (r = 0.91, P < 0.0001) and 42 (r = 0.99, P < 0.0001) WAIT, indicating visual bermudagrass cover estimates increased proportionally with cover determined from line-intersect analysis (Table 2). These findings agree with Hoyle et al (2013), who reported correlations between visual cover estimates of large crabgrass [Digitaria sanguinalis (L.) Scop. ], a common weed in turfgrass systems, and lineintersect analysis were r = 0.93 to 0.98 (P < 0.001) across two experimental runs.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Pearson correlation coefficients showed a strong positive relationship between cover determined via visual estimates and lineintersect analysis in North Carolina at 15 (r = 0.97, P < 0.0001) and 46 (r = 0.92, P < 0.0001) WAIT, as well as in Texas at 16 (r = 0.91, P < 0.0001) and 42 (r = 0.99, P < 0.0001) WAIT, indicating visual bermudagrass cover estimates increased proportionally with cover determined from line-intersect analysis (Table 2). These findings agree with Hoyle et al (2013), who reported correlations between visual cover estimates of large crabgrass [Digitaria sanguinalis (L.) Scop. ], a common weed in turfgrass systems, and lineintersect analysis were r = 0.93 to 0.98 (P < 0.001) across two experimental runs.…”
Section: Resultssupporting
confidence: 92%
“…Bermudagrass cover was also determined by line-intersect analysis at 15 and 46 WAIT in North Carolina (0.1 • 0.1 m, 322 intersections), and 16 and 42 WAIT in Texas (0.1 • 0.1 m, 792 intersections). Intersections with bermudagrass beneath them were summed and divided by the total intersects to estimate percent cover (Hoyle et al, 2013).…”
mentioning
confidence: 99%
“…Pearson correlation coefficients showed a strong positive relationship between visual cover estimates and zoysiagrass intersection counts at 40 ( r = 0.86, P < 0.001), 90 ( r = 0.87, P < 0.001), and 125 ( r = 0.91, P < 0.001) WAIE, indicating that visual zoysiagrass cover estimates increased with increased intersection counts. These findings agree with Hoyle et al (2013), as reported correlations between visual turfgrass cover estimates and line intersect analysis were r = 0.93 and 0.98 ( P < 0.001) in years 1 and 2, respectively. Therefore, visual zoysiagrass cover estimate data are presented to progressively identify variables that resulted in successful sod establishment along guardrails, arbitrarily set at ≥60% cover, and implications for in situ implementation.…”
Section: Resultssupporting
confidence: 92%
“…The grid was partitioned into an inner grid (0.53 by 2.4 m) to quantify the original sod strip cover, and outer regions (two, 0.25 by 2.4 m) on both sides of the strip to quantify sod spread. Sod spread was calculated within a plot using the following equation: %spread = [(Zintersections/Tintersections)×100]where Z intersections and T intersections equaled the number of intersections with zoysiagrass present outside of the original sod strip and the total number of intersections (92) outside of the original sod strip, respectively (Hoyle et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Thompson in accordance with turfgrass standards for effectively measuring coverage (Hoyle, Yelverton, & Gannon, 2013;Thompson, personal communication, 2015). The From this experiment, we can conclude that the seedbank is not the variable controlling the successful invasion of E. calycina.…”
mentioning
confidence: 99%